Sistem Monitoring Penetasan Telur Penyu Menggunakan Mikrokontroler NodeMCU ESP8266 dan Protokol MQTT dengan Notifikasi Berbasis Telegram Messenger - Putu Ivan Adi Guna; I Made Arsa Suyadnya; I Gusti Agung Pt Raka Agung (Journal of Computer Science and Informatics Engineering (J-Cosine), 2018)
Sea turtle has protected status because of their endangered existence. To prevent turtle extinction is by organizing turtle conservation activities. Moving the turtle eggs is one of turtle conservation activities. After moved, the eggs are monitored until they hatch and released to the sea. Monitoring of these turtle eggs is manually every day and make it difficult for officers. To help officers, author made an automatic monitoring system. The monitoring system using ultrasonic sensors and NodeMCU ESP8266 which will send data via MQTT. On the server there is a webserver to process data from hardware. There is also a telegram messenger notification that will appear when there is a change on the height of sand. With this monitoring system, it is expected to help the turtle conservation officer to move the turtles that have been hatched at the right time and monitor the eggs automatically.